Poor reduction of HIV-1 RNA titres in nucleoside reverse transcriptase inhibitor experienced patients treated with indinavir combination therapy. Issue 5 (1st October 1999) - Ball, J K; Rowe, T; Curran, R; Irving, W L; Beards, G M; Sontag, G; Youle, M; Moyle, G; Pillay, D
Abstract : OBJECTIVES: The long term effectiveness of combination therapy at reducing viral loads in seminal fluid and blood plasma obtained from HIV-1 infected men who had undergone previous antiretroviral therapy was assessed. METHODS: Samples of semen and blood were obtained from a cohort of 12 nucleoside reverse transcriptase inhibitor experienced men before and during 25-68 weeks of combination therapy, which included the protease inhibitor indinavir. HIV-1 RNA titres present in the cell free blood and seminal plasma samples were determined using the nucleic acid sequence based amplification (NASBA)/Nuclisens assay system. RESULTS: Viral RNA was detected in 9/12 and 7/12 baseline blood plasma and seminal plasma samples, with median viral titres of 10(4.81) and 10(4.56) per ml, respectively. By the end of the study period the detection rates of HIV RNA in the blood and seminal plasma samples were 5/12 and 2/12, respectively, with the median viral titres below the assay cut off level for both sample types. Of the nine patients who had detectable viral RNA in the baseline sample, only three cleared virus from both compartments by the end of the study. CONCLUSIONS: These data show that stable reduction of blood and seminal fluid viral titres is not achievable in a significant proportion of nucleoside reverse transcriptase inhibitor experienced men.